Cultural Competence and Nursing Work Environment: Impact on Culturally Congruent Care in Portuguese Multicultural Healthcare Units - Teixeira, Gisela (2024)
Cultural competence is central to ensuring effective culturally congruent care to patients and fostering positive work environments, particularly in multicultural settings. Objective: This study aimed to analyse the relationship between cultural competence, the nursing work environment, and the delivery of culturally congruent care in multicultural units of a healthcare organisation in Portugal. Method: This was a quantitative, descriptive, and cross-sectional study, targeting nurses from multicultural units. Data were collected using both online and paper-based questionnaires, which included the Cultural Competence Questionnaire for Help Professionals, the Nursing Work Index—Revised Scale (NWI-R-PT), and a single question assessing nurses’ perceptions of the adequacy of the culturally congruent care they provide. Results: A moderate, positive correlation was identified between cultural competence and the Fundamentals for Nursing, while the nursing work environment was influenced by organisational support, professional category, and unit type. Discussion: The findings suggest that enhancing cultural knowledge and technical skills and reinforcing management support may positively impact culturally congruent care delivery in multicultural settings. Conclusion: This study contributes to nursing knowledge by highlighting the complex interactions between cultural competence and the work environment in Portuguese multicultural healthcare units. Future research should explore the impact of transcultural nursing leadership on multicultural work environments and in the delivery of culturally congruent care.